2015
DOI: 10.1021/acs.jpcc.5b05016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Sm1–xCaxF3–x Tysonite Solid Solution as a Solid-State Electrolyte: Relationships between Structural Features and F Ionic Conductivity

Abstract: Pure tysonite Sm1–x Ca x F3–x solid solutions for 0.05 ≤ x ≤ 0.17 have been prepared by the solid-state route. For the first time, the partial Sm1–x Ca x F3–x solid solution is investigated on the basis of structural features and ionic conductivity measurements. Powder X-ray diffraction Rietveld refinements show an unexpected decrease of the hexagonal unit cell volume related to the creation of fluorine vacancies. The local environment of F1, which is mainly responsible for the ionic conductivity, changes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 68 publications
1
44
0
2
Order By: Relevance
“…This variation is odd compared to that observed for Sm1−xCaxF3−x in which the fluoride anionic vacancies segregate around Ca 2+ . 17 In Ce1−xSrxF3−x, the Sr 2+ cations exert a chemical pressure, weaker than that of larger Ba 2+ in La1−xBaxF3−x that contributes to the enlargement of the interslab space only ( Fig. 1 and 3).…”
Section: Xrd Characterization and Structural Featuresmentioning
confidence: 99%
“…This variation is odd compared to that observed for Sm1−xCaxF3−x in which the fluoride anionic vacancies segregate around Ca 2+ . 17 In Ce1−xSrxF3−x, the Sr 2+ cations exert a chemical pressure, weaker than that of larger Ba 2+ in La1−xBaxF3−x that contributes to the enlargement of the interslab space only ( Fig. 1 and 3).…”
Section: Xrd Characterization and Structural Featuresmentioning
confidence: 99%
“…[295] This technique achieved ah igh ionic conductivity comparable to that of the single-crystal samples.T he microstructural study indicated that the F1 site (Figure 21 a) with the anion vacancies is the main contributor to fluorine mobility.T he same group used as imilar method to prepare solid solutions of the pure tysonites Sm 1Àx Ca x F 3Àx and Ce 1Àx Sr x F 3Àx ,w hich possessed the highest room-temperature ionic conductivities of 1 10 À4 and 3 10 À4 Scm À1 for the optimum compositions of Sm 0.95 Ca 0.05 F 2.95 and Ce 0.975 Sr 0.025 F 2.975 ,r espectively. [296,297] However,t heir application in the full battery is limited by their mechanical incompatibility with electrode powder materials.…”
Section: Fluoride-ion Batteriesmentioning
confidence: 99%
“…Die gleiche Gruppe verwendete eine ähnliche Methode, um die Sm 1− x Ca x F 3− x ‐ und Ce 1− x Sr x F 3− x ‐Tysonit‐Mischkristalle zur präparieren, welche die bei Raumtemperatur höchsten Ionenleitfähigkeiten von 1×10 −4 bzw. 3×10 −4 S cm −1 für die optimalen Zusammensetzungen von Sm 0.95 Ca 0.05 F 2.95 und Ce 0.975 Sr 0.025 F 2.975 besaßen . Allerdings ist ihre Anwendung in der aufgeladenen Batterie aufgrund ihrer mechanischen Inkompatibilität mit Elektrodenpulvermaterialien begrenzt.…”
Section: Halogenid‐ionen‐batterienunclassified
“…Aufsätze optimalen Zusammensetzungen von Sm 0.95 Ca 0.05 F 2.95 und Ce 0.975 Sr 0.025 F 2.975 besaßen. [296,297] Allerdings ist ihre Anwendung in der aufgeladenen Batterie aufgrund ihrer mechanischen Inkompatibilitätm it Elektrodenpulvermaterialien begrenzt.…”
Section: Angewandte Chemieunclassified